Characterization of the Copper transporters from Lotus spp.: and their involvement under flooding conditions - Escaray, Francisco J. (2019)
Forage legumes are an important livestock nutritional resource, which includes essential metals, such as copper. Particularly, the high prevalence of hypocuprosis causes important economic losses to Argentinian cattle agrosystems. Copper deficiency in cattle is partially due to its low content in forage produced by natural grassland, and is exacerbated by flooding conditions. Previous results indicated that incorporation of Lotus spp. into natural grassland increases forage nutritional quality, including higher copper levels. However, the biological processes and molecular mechanisms involved in copper uptake by Lotus spp. remain poorly understood. Here, we identify four genes that encode putative members of the Lotus copper transporter family, denoted COPT in higher plants. A heterologous functional complementation assay of the Saccharomyces cerevisiae ctr1∆ctr3∆ strain, which lacks the corresponding yeast copper transporters, with the putative Lotus COPT proteins shows a partial rescue of the yeast phenotypes in restrictive media. Under partial submergence conditions, the copper content of L. japonicus plants decreases and the expression of two Lotus COPT genes is induced. These results strongly suggest that the Lotus COPT proteins identified in this work function in copper uptake. In addition, the fact that environmental conditions affect the expression of certain COPT genes supports their involvement in adaptive mechanisms and envisages putative biotechnological strategies to improve cattle copper nutrition.